Financial distress identification among energy sector companies listed in bursa Malaysia - Wahyu Setia, Budi (2021)
The main objective of this study is to identify financial distress of Energy Companies listed in Bursa Malaysia. The study indicates a strong significance of the variable in determining financial distress using three different models which is Altman Z-Score Model, Grover Model and Zmijewski Model. The study adopts quantitative research method of secondary source was used to collect data from annual financial report of all the energy companies listed in Bursa Malaysia. The period of study is prior Covid 19 crisis which is from 2016 to 2020. The descriptive and comparative analysis method has been used for the study and this model is developed to compare the independent variables. The descriptive analysis in this study shows that Altman Z-Score model is the most significant model to predict financial failure of the firms. While the comparative analysis shows there is no significant difference between Altman and Grover, Altman and Zmijewski as well as Grover and Zmijewski.